Myeloperoxidase and adenosine-deaminase levels in the pleural fluid leakage induced by carrageenan in the mouse model of pleurisy. - Fröde, T S (2001)
BACKGROUND: Although myeloperoxidase (MPO) and adenosine-deaminase (ADA) levels are markers of activated leukocytes, both enzymes have not been currently addressed in inflammation models. AIMS: This study evaluates whether the concentrations of these enzymes are significantly correlated with the content of leukocytes in a pleurisy model. METHODS: The pleurisy was induced by carrageenan (1%) in mice, and the parameters analyzed 4 and 48 h after. RESULTS: After the induction of inflammation (4h), MPO and ADA levels peaked in parallel to neutrophils (p<0.01). Regarding the second phase of pleurisy (48 h), the highest concentrations of ADA were detected in parallel to the highest levels of mononuclears (p<0.01). At this time, MPO levels and neutrophils remained elevated, although at lower levels than those found at 4 h. A significant positive correlation was found among neutrophiLs and MPO, and mononuclears and ADA (p<0.01). CONCLUSIONS: These findings support the evidence that both enzymes are markers of the inflammatory process, and provide new tools for a better understanding of the immunoregulatory pathways that occur in inflammation.